BARCAS Y BARCAJE EN MEDELLÍN (C. 1449 – C. 1511). - Clemente Ramos, Julián (Riparia, 2016)
<span style="font-family: ’Times New Roman’; font-size: 12pt; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: ES; mso-bidi-font-size: 10.0pt; mso-ansi-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">Medellín had a river port and one/two riverboats on the Guadiana. Some owners had their own boats, but only for your personal use. The town council leased the rent of boats to boatmen who managed the business. The boat toll rose moderately during the period studied, certainly conditioned by the rise in the price of boats in a context of increasing scarcity of wood. Avenues gave occasion to frequent abuses.